Genomic Microbial Epidemiology Is Needed to Comprehend the Global Problem of Antibiotic Resistance and to Improve Pathogen Diagnosis - Wyrsch, Ethan R.; Roy Chowdhury, Piklu; Chapman, Toni A.; Charles, Ian G.; Hammond, Jeffrey M.; Djordjevic, Steven P. (Frontiers in Microbiology, 2016)
Contamination of waste effluent from hospitals and intensive food animal production with antimicrobial residues is an immense global problem. Antimicrobial residues exert selection pressures that influence the acquisition of antimicrobial resistance and virulence genes in diverse microbial populations. Despite these concerns there is only a limited understanding of how antimicrobial residues contribute to the global problem of antimicrobial resistance. Furthermore, rapid detection of emerging bacterial pathogens and strains with resistance to more than one antibiotic class remains a challenge. A comprehensive, sequence-based genomic epidemiological surveillance model that captures essential microbial metadata is needed, both to improve surveillance for antimicrobial resistance and to monitor pathogen evolution. Escherichia coli is an important pathogen causing both intestinal (intestinal pathogenic E. coli: IPEC) and extraintestinal (extraintestinal pathogenic E. coli: ExPEC) disease in humans and food animals. ExPEC are the most frequently isolated Gram negative pathogen affecting human health, linked to food production practices and are often resistant to multiple antibiotics. Cattle are a known reservoir of IPEC but they are not recognised as a source of ExPEC that impact human or animal health. In contrast, poultry are a recognised source of multiple antibiotic resistant ExPEC, while swine have received comparatively less attention in this regard. Here we review what is known about ExPEC in swine and how pig production contributes to the problem of antibiotic resistance.